Knowledge and attitudes of pharmacy students related to hepatitis B virus - Vrekić, Petar; Milošević Georgiev, Andrijana (Archives of Pharmacy, 2022)
Nowdays, many viral infections have become a major burden on public health. Hepatitis B is a potentially fatal disease caused by the hepatitis B virus (HBV), which can be prevented by immunization. Therefore, the aim of the research was to assess the knowledge and attitudes of pharmacy students at the University of Belgrade regarding HBV. Two prospective cross-sectional studies were conducted during 2017. and 2022. using a purpose-built questionnaire. 583 students participated in the research, of which 300 in 2017. and 283 in 2022. Female students accounted for 77% vs 80%. 24% vs 20% knew which types of hepatitis exist, while 25% vs 35% believe that they received the vaccine at birth. 97% vs 98% think that as future health professionals they should have knowledge about the prevention of sexually transmitted infections, including HBV, while 18% vs 16% think they already acquired that knowledge. 57% vs 58% would vaccinate against HBV. A quarter of the respondents in 2017. and a fifth in 2022. believe that knowledge they acquired at the faculty about the transmission of HBV infection is adequate. The obtained results show that the knowledge of pharmacy students about HBV decreased in 2022. compared to 2017. although the faculty increases importance on this topic. Increased number of students who would vaccinate against HBV is encouraging. Therefore, it is necessary to emphasize the importance about risk, prevention and increase awareness of vaccination benefits for pharmacy students.